Feasibility of implementing an innovative manual handling risk assessment training program for staff working in long-term care - Natasha K Brusco; Christine Graven; Leanne Boyd; Helen Kugler; Helen Dawes; Helen Rawson; Lynne Clayton; Suzanna Tan; Victoria A Goodwin; Abi J Hall; Nicholas F Taylor (BMC, 2023)
Abstract Background The Risk Assessment for moving Individuals SafEly (RAISE) program is a hospital-based manual handling nursing training program. RAISE involves upskilling on continual risk assessment during patient-assisted movements. RAISE aims to optimise staff and patient safety while providing the patient with movement and rehabilitation opportunities. Implementation of RAISE in the hospital setting has been established. The aim of this study was to explore the feasibility of implementing RAISE in the long-term care setting. Methods We examined three feasibility domains: acceptability, practicality, and limited efficacy (observed nursing behaviour change which has the potential to reduce nursing injuries), using a prospective pilot pre-post design in the long-term care setting. Staff completed a 4-hour training session on RAISE delivered by two physiotherapists, followed by 8 h of supported behaviour change in the workplace. Staff acceptability and practicality of incorporating risk assessment strategies into manual handling approaches were explored through pre- and post-training staff surveys and a semi-structured interview. Resident acceptability of manual handling practices was explored via survey data collected after the RAISE training. Pre to post-training changes in staff knowledge and behaviour were examined through the pre- and post-training staff survey, and observation of staff assisting resident movement. Results Two enrolled nurses and five residents participated. Staff reported the RAISE program was acceptable and practical to implement in the long-term care setting. There were no adverse events or safety concerns. Staff reported the RAISE program provided guidance and enhanced staff empowerment to make decisions during assisted resident movement. There were 26 observed resident-staff manual handling interactions recorded, with 13 pre-training and 13 post-training. Post-training, RAISE skills had improved and were completed 100% of the time, except for completing a physical risk assessment which improved from 46 to 85%, demonstrating limited efficacy. Residents reported it's important for staff to be trained on how to assist them to mobilise and they found the concept of the RAISE program acceptable. Conclusions This pilot study supports the feasibility of long-term care facilities participating in future studies testing the effectiveness and cost-effectiveness of the Risk Assessment for moving Individuals SafEly (RAISE) patient and resident manual handling program.